Recent pharmacological approaches for the treatment of renal cell carcinoma - Alimohammadi, Arman; Fajkovic, Harun; Remzi, Mesut; Shariat, Shahrokh; Schmidinger, Manuela (Expert review of clinical pharmacology, 2022)
INTRODUCTION: Therapies combining either two immune check-point inhibitors (ICIs) or an ICI and a tyrosine kinase inhibitor (TKI) have been shown to improve overall survival (OS), progression-free survival (PFS) and objective response rates (ORR) in metastatic renal cell carcinoma (mRCC); moreover, unprecedented rates of complete remission (CR) have been reported. AREAS COVERED: Among six randomized trials of ICI combinations, four have outperformed the TKI sunitinib in terms of OS. The CheckMate 214 trial investigated the combination of nivolumab (a programmed cell death protein 1 [PD-1] inhibitor) and ipilimumab (a cytotoxic T-lymphocyte antigen-4 [CTLA-4)] inhibitor). Three other trials evaluated combinations of an ICI and a TKI. These combinations are: 1) pembrolizumab (PD-1 inhibitor) plus axitinib, 2) nivolumab plus cabozantinib, and 3) pembrolizumab plus lenvatinib. This short review addresses the findings of these trials, comparing outcomes and discussing the challenges of decision-making in clinical practice. EXPERT OPINION: Not all patients benefit from ICI combinations. Predictive biomarkers and new therapeutic approaches are urgently needed to overcome treatment failures. A growing understanding of immune escape mechanisms and the interplay between the immune response and the gut microbiota may offer additional rescue strategies beyond ICIs and TKIs.
Keywords: nádory ledvin; Ipilimumab; karcinom z renálních buněk; Axitinib; Carcinoma, Renal Cell; axitinib; Sunitinib; Humans; lidé; Kidney Neoplasms; sunitinib; ipilimumab